Chemical composition of essential oil from Lindera subumbelliflora Kosterm and its effect on the susceptibility and biofilm activities of Candida albicans and Streptococcus mutans - Wan Mohd Nuzul Hakimi W Salleh (Tanjung Malim, 2023)
Chemical composition of essential oil from Lindera subumbelliflora Kosterm and its effect on the susceptibility and biofilm activities of Candida albicans and Streptococcus mutans by Wan Mohd Nuzul Hakimi W Salleh